Effectiveness of Behavioral Activation Treatment on Marital Intimacy and Sexual Satisfaction of Women During Premenopause - Soolmaz Eisanezhad Boshehri; Zahra DashtBozorgi (Iranian Association of Health Education and Health Promotion, 2018)
Background and Objective: Among women's main problems during premenopause, difficulty in marital intimacy and sexual satisfaction can be noted. So, present research aimed to investigate the effectiveness of behavioral activation treatment on marital intimacy and sexual satisfaction of women during premenopause. Methods: This was a quasy-experimental research with a pre-test and post-test designed for experimental and control groups. The statistical population included all women during premenopause of Ahvaz city in 2016. 30 woman were selected by available sampling method and randomly assigned to two equal groups. The experimental group was trained about behavioral activation treatment in 8 sessions of 90 minutes. The groups completed the questionnaires of marital intimacy and sexual satisfaction as a pre-test and post-test. The data were analyzed using SPSS-19 software and multivariate analysis of covariance method. Results: The results showed there was a significant difference between the experimental group and the control group on marital intimacy and sexual satisfaction. In other words behavioral activation treatment significantly led to increase marital intimacy and sexual satisfaction of women during premenopause (P<0/05).   Conclusion: Due to the results behavioral activation treatment can increase the rate of marital intimacy and sexual satisfaction of women during premenopause, so counselors and therapists can use mentioned treatment method to increase marital intimacy and sexual satisfaction.